Metode Data Mining Klasifikasi Pada Kualitas Pelayanan Terhadap Nasabah Bank Syariah Mandiri dengan Model C4.5 - Supriadi, Ari; P, Poningsih; Qurniawan, Hendry (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Customer satisfaction is the most important thing in assessing the level of management and services provided by the bank to its customers. The existence of banking services in society is indeed more profitable, especially in the economic sector, where economic actors are more free to carry out the process of economic activities to support survival. Data mining is an analysis of observations of large amounts of data to find relationships that are not known beforehand, data processed by the data mining method will produce a new knowledge sourced from old data, the results of processing can be used to determine future decisions. Using the C4.5 algorithm will predict which aspects are more dominant towards customer satisfaction. The data source of this research was collected based on a questionnaire (questionnaire) filled out by customers of Bank Syariah Mandiri in Pematangsiantar City. Data will be processed by calculating the value of entropy, calculating the gain value. So that the final results obtained in the form of a decision tree are expected to be input to the Bank Syariah Mandiri in Pematangsiantar City in maintaining the quality of its services to customers and improving the quality so that customers are always satisfied with the services provided